150 Years of Economic Progress for African American Men: Measuring Outcomes and Sizing Up Roadblocks. Issue 3 (2nd September 2017) - Wanamaker, Marianne H
ABSTRACT: This article uses data on relative incomes to measure the economic convergence (or lack thereof) of African American men over time, and reviews current research in economic history on the struggle for economic equality for African American men in the United States since the end of the Civil War in 1865. The contents of this paper were originally presented at the University of Stellenbosch Laboratory for the Economics of Africa's Past (LEAP) Lecture on 6 December 2016.